Comparative in vivo activities of rifabutin and rifapentine against Mycobacterium avium complex. - Klemens, S P (Antimicrob Agents Chemother, 1994)
The dose-response activity of rifabutin and the comparative activities of rifabutin and rifapentine were evaluated in the beige mouse model of disseminated Mycobacterium avium complex (MAC) infection. In the dose-response study, mice were infected intravenously with approximately 10(7) viable M. avium ATCC 49601. Treatment with rifabutin at 10, 20, or 40 mg/kg of body weight was started 7 days postinfection and was administered daily for 10 days. The mice were sacrificed 3 to 5 days after the last dose. Spleens, livers, and lungs were homogenized, and viable cell counts were determined by serial dilution and plating onto Middlebrook 7H10 agar. A dose-related reduction in MAC cell counts in the organs was noted for this MAC isolate. The comparative activities of rifabutin and rifapentine were determined against a total of five MAC isolates in the beige mouse model. Rifabutin or rifapentine (20 mg/kg each) was administered to infected mice for 10 days. Groups of treated mice were compared with untreated control animals. Despite favorable in vitro susceptibility results, rifabutin and rifapentine had activities in the spleens against only two of the five MAC isolates. For these two MAC isolates, rifabutin was more active than rifapentine. These agents had activities in the lungs against three of five isolates. Further study of rifabutin or rifapentine against a broader range of clinical isolates in a murine infection model may be useful as part of the continuing development of newer rifamycins as anti-MAC agents.